2022
DOI: 10.2319/021922-155.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maxillary and mandibular extrusion arches on dentoskeletal changes in adults with anterior open bite: a quantitative analysis

Abstract: Objective To quantify dentoskeletal changes accompanying the use of extrusion arches during the treatment of anterior open bite (AOB) in adults. Materials and Methods A total of 23 adult patients with an AOB of −3.05 mm ± 1.27 mm were treated with upper and lower extrusion arches after the alignment phase. Lateral cephalograms were taken before placement of the extrusion arch, immediately after closure of the open bite (T2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
2
2
1
2
Order By: Relevance
“…Regarding extrusion of the anterior teeth, these findings agree with those of Hammad et al 17 The results of this study revealed that there was significant palatal tipping of the maxillary incisors by -5.78±0.77°, and there was no significant change in the inclination of the lower incisors. These results can be explained as there was an uprighting moment produced by the extrusion arch on the upper incisors, 11 effect that is favorable in patients with labial inclination of the maxillary incisors.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Regarding extrusion of the anterior teeth, these findings agree with those of Hammad et al 17 The results of this study revealed that there was significant palatal tipping of the maxillary incisors by -5.78±0.77°, and there was no significant change in the inclination of the lower incisors. These results can be explained as there was an uprighting moment produced by the extrusion arch on the upper incisors, 11 effect that is favorable in patients with labial inclination of the maxillary incisors.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, this study showed that the interincisal angle increased significantly by 9.94±1.09°, due to the palatal tipping of the anterior teeth. These results were consistent with those of Hammad et al, 17 Atsawasuwan et al, 20 and de Brito Vasconcelos et al 15 As a result of incisor palatal tipping, the overjet reduced significantly by 1.58± 0.5 mm.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Відомо, кількість дорослого населення, що звертається за ортодонтичною допомогою, протягом останніх років за даними авторитетних вчених зросла на 17-23 % та має тенденцію до збільшення [1,2]. Глибокий прикус -достатньо розповсюджена патологія, яка складає близько до 20 % усіх зубо-щелепних аномалій.…”
Section: вступunclassified
“…Важливість цього питання обумовлена значною розповсюдженістю даної анормальності, регулярним під-вищенням зафіксованих звернень пацієнтів, різноликістю клінічних проявів, значними труднощами при проведенні діагностики, диференційної діагностики та лікування, що потребує ґрунтовного міждисциплінарного рішення [5,6]. Останнім часом спостерігається тенденція до зростання кількості стоматологічних пацієнтів, які скаржаться на порушення функціональної оклюзії, яка спричинена реконструктивними реставраціями при наявній патології прикусу [7,8].…”
Section: вступunclassified